MiR‐30a inhibits androgen‐independent growth of prostate cancer via targeting MYBL2, FOXD1, and SOX4. Issue 9 (15th April 2020) - Li, Xinjun; Jiao, Meng; Hu, Jing; Qi, Mei; Zhang, Jing; Zhao, Mingfeng; Liu, Hui; Xiong, Xueting; Dong, Xuesen; Han, Bo
Abstract: Background: Castrate‐resistant prostate cancer (CRPC) is an aggressive and lethal disease. The pathogenesis of CRPC is not fully understood and novel therapeutic targets need to be identified to improve the patients' prognosis. MicroRNA‐30a (miR‐30a) has been demonstrated to be a tumor suppressor in many types of solid malignancies. However, its role in androgen‐independent (AI) growth of prostate cancer (PCa) received limited attention as yet. Methods: The clinical association of miR‐30a and its potential targets with AI growth was characterized by bioinformatics analyses. Regulation of cell proliferation and colony formation rates by miR‐30a were tested using PCa cell models. Xenograft models were used to measure the regulation of prostate tumor growth by miR‐30a. The real‐time quantitative polymerase chain reaction was used to validate whether miR‐30a and its targets regulate cell cycle control genes and androgen receptor (AR)‐dependent transcription. Bioinformatics tools, Western blot, and luciferase reporter assays were utilized to identify miR‐30a targets. Results: Bioinformatic analysis showed that low expression of miR‐30a is associated with castration resistance of PCa patients and poor outcomes. Transfection of miR‐30a mimics inhibited the AI growth of PCa cells in vitro and in vivo. Upregulation of miR‐30a in 22RV1 cells altered the expression of cell cycle control genes and AR‐mediated transcription, while downregulation of miR‐30a in LNCaP cells had the opposite effects to AR‐mediated transcription. MYBL2, FOXD1, and SOX4 were identified as miR‐30a targets. Downregulation of MYBL2, FOXD1, and SOX4 affected the expression of cell cycle control genes and AR‐mediated transcription and suppressed the AI growth of 22RV1 cells. Conclusions: Our results suggest that miR‐30a inhibits AI growth of PCa by targeting MYBL2, FOXD1, and SOX4. They provide novel insights into developing new treatment strategies for CRPC.